2010
DOI: 10.1007/s10903-010-9383-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Urge Urinary Incontinence (UUI) Among Older Mexican–American Men: Risk Factors and Psycho-Social Consequences

Abstract: Extant literature on Urge Urinary Incontinence (UUI) focuses on women and non-Hispanic White and little is known about ethnic minority men. We analyzed 700 Mexican-American men aged 75 and older from the fifth Wave (2004/5) of the Hispanic Established Population for the Epidemologic Study of the Elderly. Logistic regression analyses examined risk factors for selfreported UUI and the impact of UUI on mental health and social support. Twenty-nine percent reported having difficulty holding their urine until they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
2
18
2
Order By: Relevance
“…Our findings, indicating male UI was associated with age, mobility, and self‐care ability, support previous results that aging and restriction in activities of daily living are the risk factors for male UI …”
Section: Discussionsupporting
confidence: 91%
“…Our findings, indicating male UI was associated with age, mobility, and self‐care ability, support previous results that aging and restriction in activities of daily living are the risk factors for male UI …”
Section: Discussionsupporting
confidence: 91%
“…A longitudinal study of 796 elderly (aged ≥ 65 years) Australian adults found that UUI occasionally or often ( n = 220) was significantly (p < 0.01) associated with depression (score ≥ 3 on Depression Scale of Psychogeriatric Assessment Scales), with greater UUI frequency associated with an increased likelihood of depression in women only . Additionally, clinical depression (CES‐D score ≥ 16) was significantly associated with UUI (adjusted OR = 2.9; 95% CI: 1.7–4.9) for Mexican‐American men aged ≥ 75 years in the community‐based Hispanic Established Population for the Epidemiological Study of the Elderly (Hispanic EPESE), based on a multivariate model .…”
Section: Resultsmentioning
confidence: 99%
“…, Gerst et al . ). The infrequent use of informational brochures is consistent with the findings of studies with regard to other care problems and the use of informational brochures as structural indicators (Schoberer et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Gerst et al . ). Incontinence has significant psychological and social impacts, places major limitations on the quality of life (Hägglund , Hayder & Schnepp , De Mello Portella et al .…”
Section: Introductionmentioning
confidence: 97%